Glycyrrhizic Acid and Its Hydrolyzed Metabolite 18β-Glycyrrhetinic Acid as Specific Ligands for Targeting Nanosystems in the Treatment of Liver Cancer - Luciano A. Stecanella; Antonio P. R. Bitencourt; Gustavo Richter Vaz; Eride Quarta; José O. C. Silva Júnior; Alessandra Rossi (MDPI AG, 2021)
Glycyrrhizic acid and its hydrolyzed metabolite 18β-glycyrrhetinic acid, obtained from the plant Glycyrrhiza glabra, have numerous pharmacological activities, such as anti-inflammatory, anti-ulcerative, antiallergic, immunomodulatory, antiviral, antitumor, hepatoprotective, and antioxidant effects, and others. In addition to the pharmacological activities, in the 1980s, an interaction and uptake of these molecules by the liver was verified, which was later confirmed by other studies through the discovery of specific receptors in the hepatocytes. The presence of these specific receptors in the liver led to vectorization and delivery of drugs, by the introduction of glycyrrhizic acid or glycyrrhetinic acid on the surface of nanosystems, for the treatment of liver diseases. This review describes experimental evidence of vectorization by conjugating glycyrrhizic acid or glycyrrhetinic acid to nanosystems and delivery of antitumor drugs for the treatment of liver cancer and also describes the techniques used to perform this conjugation. We have shown that due to the existence of specific receptors for these molecules, in addition to the targeting of nanosystems to hepatocytes, nanosystems having glycyrrhizic acid or glycyrrhetinic acid on their surface had the same therapeutic effect in a significantly lower dose compared to the free drug and unconjugated nanosystems, with consequent reduction of side effects and toxicity.